NURTURING PERFORMANCE THROUGH ISLAMIC WORK VALUES: THE ROLE OF ETHICS, CULTURE, AND MOTIVATION - Nugraha, Satya; Zaroni, Akhmad Nur; Komariah, Kokom (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The role of Islamic values in the workplace is an important aspect in improving performance and the quality of human resources. In this context, Islamic work ethics, Islamic work culture, and Islamic work motivation are believed to contribute to shaping productive work behavior. This study aims to analyze the influence of Islamic work ethics, Islamic work culture, and Islamic work motivation on employee performance. The method used is a quantitative approach with multiple linear regression analysis. Data were obtained through the distribution of questionnaires to respondents who met the research criteria. The results